Molecular Diversity Analysis in Potato (Solanum tuberosum L.) through RAPD Markers (SAARC Journal of Agriculture, 2014)
Random Amplified Polymorphic DNA (RAPD) markers were used to study the molecular diversity of 12 popular potato varieties in Bangladesh. DNA was extracted from tender leaf sample for PCR amplification. The PCR amplified DNA profile was visualized on 2% agarose gel, staining with ethidium bromide. Eight RAPD primers were used to evaluate the genetic diversity of potato varieties. Some total of 36 DNA fragments were amplified and out of them 24 were polymorphic. Those primers generated 61.53% of polymorphic DNA band. The primer OPX 04 produced highest (9) number of DNA band and out of 9 amplicon 6 were polymorphic. Lowest number of amplification was observed in the primer OPA-17 and it was only 3. The highest Neis genetic distance (0.9701) was noticed between the variety Granola and Provinto. The highest (0.8205) number of genetic identity/similarity was observed between the varieties Cardinal and Diamant. The unweighted pair group method of arithmetic mean (UPGMA) dendrogram based on Neis genetic distance revealed that the 12 varieties followed into two main clusters. The present finding showed that there was high level of genetic diversity among the varieties which can be used for parental selection in potato breeding program. DOI: http://dx.doi.org/10.3329/sja.v11i2.18405 SAARC J. Agri., 11(2): 95-102 (2013)